Study on the Mechanical Response of a Dense Pipeline Adjacent to the Shallow Tunnel - Bo Wu; Weiqiang Zheng; Fangyu Guo; Shixiang Xu; Wenhua Zhu; Bo Xu; Yong Zhang (Advances in Materials Science and Engineering)
This paper aims to address the issue of disturbance caused by excavation tunnel construction on nearby dense pipelines. Relying on the actual project of Nanchang Metro, the three-dimensional finite element numerical simulation method is used to establish a multi-condition numerical model. At the same time, key influencing factors such as the clear distance, intersection angle, surrounding rock parameter, and construction method are considered. The mechanical response of the dense pipeline adjacent to the dug tunnel was systematically studied, and the influence of key factors on the mechanical behavior of the pipeline was analyzed. The results show that when using the CRD method for construction and grouting reinforcement of the surrounding strata of the tunnel, the maximum settlement of the vault is located at the vault of the right guide tunnel, and the maximum settlement value is located at the bottom of the rainwater pipe directly above the tunnel. The vertical displacement, maximum principal stress, and minimum principal stress of the pipeline are arranged in descending order for the full-face, stepped method, and CRD method. The greater the disturbance to the soil caused by the construction method, the more unfavorable the effect on the pipeline.